2018
DOI: 10.2807/1560-7917.es.2018.23.27.1700497
|View full text |Cite
|
Sign up to set email alerts
|

Sharing more than friendship – transmission of NDM-5 ST167 and CTX-M-9 ST69 Escherichia coli between dogs and humans in a family, Finland, 2015

Abstract: IntroductionCarbapenemase-producing Enterobacteriaceae (CPE) have rarely been reported in dogs, and never in animals in Finland. However, in April 2015, two meropenem-resistant Escherichia coli were identified from two dogs in one family. Both dogs suffered from chronic otitis externa. Methods: Epidemiological and molecular investigations (pulsed-field gel electrophoresis (PFGE), multilocus sequence typing) were conducted to investigate the source of infection and transmission routes. Results: In both dogs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 36 publications
2
70
0
1
Order By: Relevance
“…aureus in 24 h while at 49 MIC a more than 3 log 10 reduction was observed after 4 h. Previous studies have also shown cinnamaldehyde as a potential antimicrobial agent against Staph. aureus (Ye et al 2013;Garcia-Salinas et al 2018). Our findings suggest the potential use of both cinnamon oil and cinnamaldehyde for the topical treatment of infections in dogs, but the latter as a more promising bactericidal compound.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…aureus in 24 h while at 49 MIC a more than 3 log 10 reduction was observed after 4 h. Previous studies have also shown cinnamaldehyde as a potential antimicrobial agent against Staph. aureus (Ye et al 2013;Garcia-Salinas et al 2018). Our findings suggest the potential use of both cinnamon oil and cinnamaldehyde for the topical treatment of infections in dogs, but the latter as a more promising bactericidal compound.…”
Section: Discussionmentioning
confidence: 74%
“…; Grönthal et al . ). In addition, many antimicrobial agents, used for veterinary purposes to treat a wide range of microbial infections across many animal species, are within the same class as human therapeutic drugs, potentially increasing AMR in humans (Wijesekara et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For MRSP/MRSA, two swabs were taken: one from the nares and the mouth/lip commissure, and one from the perianal region . For ESBL, the swab was taken from the rectum . The swabs were processed and bacterial identification, including susceptibility testing and Pulsed Field Gel Electrophoresis (PFG) analysis, was performed as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, no carbapenem or colistin resistance genes were found in this study. Two carbapenemases positive E. coli were found in two dogs in 2015 (Grönthal et al, ), and recently on two occasions colistin‐resistant strains have been found in street dogs imported from Russia (Finnish Food Safety Authority, ; University of Helsinki, ). As this study shows how frequent companion animal practice is among veterinarians, the situation should be closely monitored as infection pressure might grow rapidly due to dog imports.…”
Section: Discussionmentioning
confidence: 99%